Exendin-4 protects rat islets against loss of viability and function induced by brain death - Carlessi, Rodrigo; Lemos, N.; Dias, A.; Oliveira, F.; Brondani, L.; Canani, L.; Bauer, A.; Leitão, C.; Crispim, D. (Elsevier Ireland Ltd, 2014)
Islet quality loss after isolation from brain-dead donors still hinders the implementation of human islet transplantation for treatment of type 1 diabetes. In this scenario, systemic inflammation elicited by donor brain death (BD) is among the main factors influencing islet viability and functional impairment. Exendin-4 is largely recognized to promote anti-inflammatory and cytoprotective effects on ß-cells. Therefore, we hypothesized that administration of exendin-4 to brain-dead donors might improve islet survival and insulin secretory capabilities. Here, using a rat model of BD, we demonstrate that exendin-4 administration to the brain-dead donors increases both islet viability and glucose-stimulated insulin secretion. In this model, exendin-4 treatment produced a significant decrease in interleukin-1ß expression in the pancreas. Furthermore, exendin-4 treatment increased the expression of superoxide dismutase-2 and prevented BD-induced elevation in uncoupling protein-2 expression. Such observations were accompanied by a reduction in gene expression of two genes often associated with endoplasmic reticulum (ER) stress response in freshly isolated islets from treated animals, C/EBP homologous protein and immunoglobulin heavy-chain binding protein. As ER stress response has been shown to be triggered by and to participate in cytokine-induced ß-cell death, we suggest that exendin-4 might exert its beneficial effects through alleviation of pancreatic inflammation and oxidative stress, which in turn could prevent islet ER stress and ß-cell death. Our findings might unveil a novel strategy to preserve islet quality from brain-dead donors. After testing in the human pancreatic islet transplantation setting, this approach might sum to the ongoing effort to achieve consistent and successful single-donor islet transplantation.